Corrigendum to: Promotion Strategy by Palu City Government to Pulling Investors Interest in Palu Special Economic Zone - Redaksi Jurnal ASPIKOM (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
After the publication of the article titled "Promotion Strategy By Palu City Government To Pulling  Investors  Interest  In  Palu  Special  Economic  Zone",  in  Jurnal  ASPIKOM  Volume  3 Nomor 4 (2018),  Muhammad Khairil as the author noted that there was a missing reference in the Introduction section page 800 (paragraph 8).